2018
DOI: 10.4236/pp.2018.96014
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Appraisal of Bidens pilosa (Asteraceae) Leaf Extracts Used in Management of Oral Lesion Pain in HIV/AIDS Patients in Rodents

Abstract: Oral lesions, diarrhoea, Pneumocystis carinii pneumonia, tuberculosis and urinary tract infections are some of the opportunistic infections (OIs) which arise when the CD4 cells of the HIV/AIDS patient fall below 200 cells/mm 3. HIV/AIDS infection complications include tissue damage from oral lesions accompanied with pains. Pain is a disagreeable sensory and sensitive experience associated with actual or potential tissue damage. This condition requires immediate treatment with analgesics and antibiotics. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
0
10
0
1
Order By: Relevance
“…Medicinally, they are known as stimulants, local anesthetics, anti-bacterial, anti-hypertensive and analgesics. This explains the use of B. pilosa in the treatment of headaches and pains 17 .…”
Section: Discussionmentioning
confidence: 93%
“…Medicinally, they are known as stimulants, local anesthetics, anti-bacterial, anti-hypertensive and analgesics. This explains the use of B. pilosa in the treatment of headaches and pains 17 .…”
Section: Discussionmentioning
confidence: 93%
“…The aqueous extract of B. pilosa contains polyacetylenes; flavonoids; flavonols; terpenoids; tannins; phlobatannins; alkaloids; saponins; steroids; sterols; cardiac glycosides; Phenol, 2, 4-Bis (1, 1-Dimethylethyl) and other phenolic compounds [18,35,29,36]. These compounds might play a role in the activities of the extracts, such as antimicrobial activity against Gram-positive and negative bacteria [29], analgesic activity [18]; anti-inflammatory [5]; hepatoprotective activity [37]; anti-plasmodial activity, [35]; anti-obesity [36]; and alleviate the dry-eye symptoms [20].…”
Section: Bioactive Compounds Of B Pilosa Plant Partsmentioning
confidence: 99%
“…The properties are no longer folklores because many studies have been proven the activities in vitro, in vivo, and ex vivo assays [3,7,9,[12][13][14][15][16][17][18][19][20][21][22][23]. Currently, the plant become a market commodity, such as dried plant powder, B. pilosa tea, extracts, and tinctures.…”
Section: Introductionmentioning
confidence: 99%
“…Some traditional plants used for the treatment of pain also have one or more of these metabolites. Compounds, such as tannins, anacardial acid present in extracts of Anacardium occidentale L [ 174 ], eugenol and linalol identified in extracts of Bidens Pilosa [ 175 , 176 ], camphor and linalool from Piper aduncum extracts [ 177 , 178 ], and carvone and geraniol from Lippia alba [ 179 ], may be involved in the potential analgesic effects of these extracts [ 174 , 180 , 181 ]. However, further studies are required to elucidate the mechanisms mediating the observed effects [ 181 ].…”
Section: The Role Of Trp Channel Agonists and Antagonists In Cancer Painmentioning
confidence: 99%